Exosomes derived from pro‐inflammatory bone marrow‐derived mesenchymal stem cells reduce inflammation and myocardial injury via mediating macrophage polarization. Issue 11 (26th September 2019) - Xu, Ruqin; Zhang, Fangcheng; Chai, Renjie; Zhou, Wenyi; Hu, Ming; Liu, Bin; Chen, Xuke; Liu, Mingke; Xu, Qiong; Liu, Ningning; Liu, Shiming
Abstract: Exosomes are served as substitutes for stem cell therapy, playing important roles in mediating heart repair during myocardial infarction injury. Evidence have indicated that lipopolysaccharide (LPS) pre‐conditioning bone marrow‐derived mesenchymal stem cells (BMSCs) and their secreted exosomes promote macrophage polarization and tissue repair in several inflammation diseases; however, it has not been fully elucidated in myocardial infarction (MI). This study aimed to investigate whether LPS‐primed BMSC‐derived exosomes could mediate inflammation and myocardial injury via macrophage polarization after MI. Here, we found that exosomes derived from BMSCs, in both Exo and L‐Exo groups, increased M2 macrophage polarization and decreased M1 macrophage polarization under LPS stimulation, which strongly depressed LPS‐dependent NF‐κB signalling pathway and partly activated the AKT1/AKT2 signalling pathway. Compared with Exo, L‐Exo had superior therapeutic effects on polarizing M2 macrophage in vitro and attenuated the post‐infarction inflammation and cardiomyocyte apoptosis by mediating macrophage polarization in mice MI model. Consequently, we have confidence in the perspective that low concentration of LPS pre‐conditioning BMSC‐derived exosomes may develop into a promising cell‐free treatment strategy for clinical treatment of MI.